Gut-Evolved Candida albicans Induces Metabolic Changes in Neutrophils - Reales-Calderon, Jose Antonio; Tso, Gloria H. W.; Tan, Alrina S. M.; Hor, Pei Xiang; Böhme, Julia; Teng, Karen W. W.; Newell, Evan W.; Singhal, Amit; Pavelka, Norman (Frontiers in Cellular and Infection Microbiology, 2021)
Serial passaging of the human fungal pathogen Candida albicans in the gastrointestinal tract of antibiotics-treated mice selects for virulence-attenuated strains. These gut-evolved strains protect the host from infection by a wide range of pathogens via trained immunity. Here, we further investigated the molecular and cellular mechanisms underlying this innate immune memory. Both Dectin-1 (the main receptor for β-glucan; a well-described immune training molecule in the fungal cell wall) and Nod2 (a receptor described to mediate BCG-induced trained immunity), were redundant for the protection induced by gut-evolved C. albicans against a virulent C. albicans strain, suggesting that gut-evolved C. albicans strains induce trained immunity via other pathways. Cytometry by time of flight (CyTOF) analysis of mouse splenocytes revealed that immunization with gut-evolved C. albicans resulted in an expansion of neutrophils and a reduction in natural killer (NK) cells, but no significant numeric changes in monocytes, macrophages or dendritic cell populations. Systemic depletion of phagocytes or neutrophils, but not of macrophages or NK cells, reduced protection mediated by gut-evolved C. albicans. Splenocytes and bone marrow cells of mice immunized with gut-evolved C. albicans demonstrated metabolic changes. In particular, splenic neutrophils displayed significantly elevated glycolytic and respiratory activity in comparison to those from mock-immunized mice. Although further investigation is required for fully deciphering the trained immunity mechanism induced by gut-evolved C. albicans strains, this data is consistent with the existence of several mechanisms of trained immunity, triggered by different training stimuli and involving different immune molecules and cell types.